Persepsi Masyarakat Terhadap Pemungutan Pajak Bumi dan Bangunan di Kecamatan Bojonegara Berbasis Digital - Wananda Purna Maulidi; Munawaroh Munawaroh (Universitas Kristen Indonesia Toraja, 2025)
The purpose of this study is to determine how the Bojonegara District's public feels about digitally based Land and Building Tax (PBB) collection, examine the variables that affect these opinions, and offer tactical suggestions to improve public support for this policy. The e-Government system for taxes is anticipated to improve the administrative process at the United Nations in the age of digital transformation by increasing efficiency, transparency, and convenience. Nonetheless, the primary challenges remain, including a lack of public awareness and a lack of openness in the way tax money is managed. In this study, the local community was surveyed using quantitative descriptive methodologies. The findings of the study indicate that while society welcomes digitization, questions remain regarding its equitable and efficient implementation. Increasing openness, educating the public, and making sure stakeholders are actively involved are all advised.